FIRST LANGUAGE ATTITUDE TOWARD THE SECOND LANGUAGE DEVELOPMENT: ENGLISH SPEAKING LEARNERS - Diana OKTAVIA; Amirul MUKMININ; Nur HABIBA; Winda TRISNAWATI; Levandra BALTI; Ridho KURNIAWAN (Linguarum Universe)
This research was conducted to investigate the students first language attitude towards their speaking ability in English language learning. The required data of this research were collected through the deep interview involving 10 participants to provide the information regarding this matter. Those participants were enrolled as the fifth semester students at English Education Department of Universitas Muhammadiyah Muara Bungo. They learn English as their third language after the local language and Indonesian language. Based on the interview result, it was found that all of participants admitted that they use the local language every day as daily communication media. Most of the participants reported that those local languages have big influence toward their ability to speak English. They explained that it occurs in term of the way they pronounce the words, chose the vocabulary, and use the expression. The participants also talked that it occurs because the environment and society where they live also uses the local language so they do not have space to practice English. However, on other hand, some participants reported that they do not get any impact from the local language toward their English-speaking skill, because they try to minimize this influence by practicing more often by watching English videos and other activities.